Metabolic and Hepatic Effects of Energy-Reduced Anti-Inflammatory Diet in Younger Adults with Obesity - Gordana Kenđel Jovanović; Ines Mrakovcic-Sutic; Sandra Pavičić Žeželj; Indira Benjak Horvat; Lucia Šuša; Dario Rahelić; Sanja Klobučar Majanović (Canadian Journal of Gastroenterology and Hepatology)
Background. Associated with epidemics of obesity, nonalcoholic fatty liver disease (NAFLD) is becoming the most prevalent liver disease worldwide. The cornerstone of therapy for NAFLD is lifestyle intervention, mainly focused on weight loss. Significant weight loss results from energy-restricted diets, regardless of macronutrient distribution. An anti-inflammatory diet was related to lower odds of NAFLD among daily alcohol drinkers and individuals with metabolic syndrome. This study aims to evaluate the effect of an energy-reduced anti-inflammatory diet on liver status in younger adults with obesity after a 6-month follow-up. Methods. A two-arm randomized controlled trial surveyed 81 participants’ (mean age, 43 years) anthropometric and body composition changes. Metabolic status was determined with glycaemic and lipid status, inflammatory status with hs-CRP, IL-6, and TNF-α, and liver status with liver enzymes, NAFLD-FLS, FLI, and FIB-4 indices. The inflammatory potential of the diet was assessed by the Dietary Inflammatory Index, DII®. Results. Energy-restricted anti-inflammatory diet resulted in significant weight loss (−7.1%, p < 0.001), in reducing the visceral adiposity (−22.3%, p < 0.001), metabolic (HOMA-IR, −15.5%; total cholesterol, −5.3%; LDL-C, −4.6%; triglycerides, −12.2%), and inflammatory biomarkers (hs-CRP, −29.5%; IL-6, −18.2%; TNF-α, −34.2%), with significant improvement of liver parameters (NAFLD-FLS, −143.4%; FLI, −14.3%; FIB-4, −2.5%). Conclusion. The study showed the effectiveness of the anti-inflammatory diet with significant improvement of liver parameters in younger adults with obesity, which may reinforce the effectiveness of nutrition-based lifestyle programs, with an anti-inflammatory dietary approach for the treatment and resolution of NAFLD.